2020
DOI: 10.1200/jop.19.00593
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Initiative to Enhance Multidisciplinary Management of Malignant Extradural Spinal Cord Compression

Abstract: PURPOSE: To determine if a quality improvement (QI) initiative could enhance multidisciplinary management of acute malignant extradural spinal cord compression (ESCC) at our institution. METHODS: The medical records of all 40 patients who received palliative radiotherapy for malignant ESCC from 2015 to 2017 were reviewed to determine the time course of key National Comprehensive Cancer Network guideline–supported workup and management steps. On the basis of the findings, a multidisciplinary group of physician … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Our pooled compliance rate of 32% for the concurrent use of steroids with radiotherapy for clinical MSCC (BoM-4) was lower than those reported in previous single-center studies [ 24 , 25 ]. In a retrospective audit of clinical practice on MSCC at a UK regional cancer center, in 42% of patients, dexamethasone had been prescribed before cancer center admission, and this increased to 96% following admission [ 24 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Our pooled compliance rate of 32% for the concurrent use of steroids with radiotherapy for clinical MSCC (BoM-4) was lower than those reported in previous single-center studies [ 24 , 25 ]. In a retrospective audit of clinical practice on MSCC at a UK regional cancer center, in 42% of patients, dexamethasone had been prescribed before cancer center admission, and this increased to 96% following admission [ 24 ].…”
Section: Discussioncontrasting
confidence: 76%
“…However, the difficulty in making the diagnosis of nonmalignant compression of the spinal cord or cauda equina has been previously highlighted in the ED literature with delays occurring in 50%–70% of cases 7,8 . Since MSCC is considered an oncologic emergency, efforts have been made to expedite the evaluation and care of these patients by prompt referral for spinal column MRI, administration of dexamethasone, and evaluation by a multidisciplinary team 9,10 …”
Section: Type Of Initial Imaging Type Of Initial Imaging As a Percent...mentioning
confidence: 99%
“…7,8 Since MSCC is considered an oncologic emergency, efforts have been made to expedite the evaluation and care of these patients by prompt referral for spinal column MRI, administration of dexamethasone, and evaluation by a multidisciplinary team. 9,10 It needs to be kept in mind that the textbook example of a patient with MSCC presenting with severe lower extremity motor weakness is the result of an evolving process in which the epidural tumor burden progressively compresses the spinal cord and finally reaches a threshold at which point the classic symptom of paralysis becomes manifest. Therefore, a patient may present for an initial evaluation due to increasing pain and lower extremity weakness at a time when a neurologic examination is not sufficient to prompt an evaluation for a MSCC but only to have the patient present a few weeks later with the classic finding of lower extremity paralysis.…”
mentioning
confidence: 99%
“…In a study by Mattes et al, which describes an educational campaign aimed at expediting and enhancing multidisciplinary care for MSCC, the use of whole-spine MRIs increased from 44% to 64% in the first year after this Quality Improvement (QI) initiative [76]. Additionally, data from the same cohort showed that the number of referrals between the initial presentation to any on MRI following the introduction of a multidisciplinary clinical pathway [76].…”
Section: Reducing Delaymentioning
confidence: 99%
“…In a study by Mattes et al, which describes an educational campaign aimed at expediting and enhancing multidisciplinary care for MSCC, the use of whole-spine MRIs increased from 44% to 64% in the first year after this Quality Improvement (QI) initiative [76]. Additionally, data from the same cohort showed that the number of referrals between the initial presentation to any on MRI following the introduction of a multidisciplinary clinical pathway [76]. Another study showed that, after the introduction of a multidisciplinary system, the incidence of neurological deficits decreased from 13.2% to 3.4%, and the improvement of neurological deficits after intervention increased from 5.3% to 28.6%, likely due to more urgent surgical intervention [80].…”
Section: Reducing Delaymentioning
confidence: 99%